HITTING TIME DISTRIBUTIONS FOR BIRTH–DEATH PROCESSES WITH BILATERAL ABSORBING BOUNDARIES. Issue 3 (13th September 2016) - Mao, Yong-Hua; Zhang, Chi
Abstract : For the birth–death process on a finite state space with bilateral boundaries, we give a simpler derivation of the hitting time distributions by h -transform and φ-transform. These transforms can then be used to construct a quick derivation of the hitting time distributions of the minimal birth–death process on a denumerable state space with exit/regular boundaries.